Achieving justice : comparative public opinion on income distribution - Aalberg, Toril (International comparative social studies, 2003)
This work provides a comparative analysis of public beliefs about social justice. What can explain the cross-national variations, and if opinions do change over time, why is this so? This text should be of interest to those interested in the relationship between public opinion and political elite.